Nonlinear Mathieu Equation and its Approximation Without a Small Parameter - He, Ji-Huan (Engineering Transactions, 2002)
In this paper, the linear and nonlinear Mathieu equations without a small parameter are considered, which cannot be solved by the perturbation techniques. However, using the variational iteration method, their periodic solutions can be readily obtained with high accuracy. In addition, some special cases have been discussed, where the perturbation solutions are meaningless even when there exists a small parameter.